Iceman Survived due to Cooling Device. (9th May 2011) - Roser, M.; Martens, F.; Storm, C.
Abstract : Although mild hypothermia treatment is part of the standard postresuscitation care today, no standard method for treatment of accidental severe hypothermia has been yet established. Different strategies including invasive and noninvasive methods have been described in the literature. We present the case of a 75-year-old man with accidental severe hypothermia (23°C) and demonstrate that using a surface cooling device with automatic controlled temperature feedback mechanism (ArcticSun2000 Medivance, Louisville, Colorado, USA) is an effective and safe method for controlled rewarming in this life-threatening setting.